EBay photography the smart way : creating great product pictures that will attract higher bids and sell your items faster - Sinclair, Joseph T. (AMACOM, 2005)
If a picture is worth a thousand words, just imagine how much a picture could be worth on eBay! In "eBay Photography the Smart Way", professional eBay expert Joseph Sinclair teams up with professional product photographer Stanley Livingston to show sellers how to instantly increase their sales and ramp up their profits! The book gives readers easy-to-follow instructions for taking better pictures, helping them show off their products to the greatest possible effect